2017
DOI: 10.1016/j.watres.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of advanced oxidation on N-nitrosodimethylamine (NDMA) formation and microbial ecology during pilot-scale biological activated carbon filtration

Abstract: Water treatment combining advanced oxidative processes with subsequent exposure to biological activated carbon (BAC) holds promise for the attenuation of recalcitrant pollutants. Here we contrast oxidation and subsequent biofiltration of treated wastewater effluent employing either ozone or UV/HO followed by BAC during pilot-scale implementation. Both treatment trains largely met target water quality goals by facilitating the removal of a suite of trace organics and bulk water parameters. N-nitrosodimethylamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…While other studies reported moderate susceptibility of sucralose to increasing ozone dose (Sundaram et al, 2020;Vatankhah et al, 2019), only minor sensitivity was observed ( Figure 2). The removal of NDMA was also limited by ozonation due to its low k O 3 (0.052 M −1 s −1 ) and low susceptibility to hydroxyl radical oxidation (k OH = 4.5 × 10 8 M −1 s −1 ), as also reported by others (Bacaro et al, 2019;Hollender et al, 2009;D. Li et al, 2017;Sundaram et al, 2020).…”
Section: For Some Compounds With Lowsupporting
confidence: 72%
See 1 more Smart Citation
“…While other studies reported moderate susceptibility of sucralose to increasing ozone dose (Sundaram et al, 2020;Vatankhah et al, 2019), only minor sensitivity was observed ( Figure 2). The removal of NDMA was also limited by ozonation due to its low k O 3 (0.052 M −1 s −1 ) and low susceptibility to hydroxyl radical oxidation (k OH = 4.5 × 10 8 M −1 s −1 ), as also reported by others (Bacaro et al, 2019;Hollender et al, 2009;D. Li et al, 2017;Sundaram et al, 2020).…”
Section: For Some Compounds With Lowsupporting
confidence: 72%
“…Organic macromolecules with highly susceptible sites for ozone oxidation, such as aromatic and amino acids functional groups, can react to form oxidation byproducts such as aldehydes, ketones, and carboxylic acids (Legube, 2003), as well as nitrosamines such as NDMA and NMOR (Bacaro et al, 2019; Bourgin et al, 2018; D. Li et al, 2017). As expected, the presence of NDMA and NMOR in ozonated effluents was also observed in a number of studies reviewed as depicted in Figure 5a and b.…”
Section: Resultsmentioning
confidence: 99%
“…NDMA has good removal in biofiltration (Bacaro et al, 2019), so it may be removed to DR below four prior to UV photolysis in the above scenario. However, if the ozonation NDMA precursors are relatively high at the site, detectable NDMA could pass through the biofiltration (Li et al, 2017). In such a case, NDMA would be a key health‐based indicator targeted by UV and could potentially qualify as a PBI.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, with biomass accumulation and shear forces exerted by hydraulic shocks, biofilms would detach from and pass through the BAC filter media, thus increasing cell density in the BAC effluent (Boon et al, 2011; Besmer and Hammes, 2016). Nevertheless, a diverse microbial biofilm community that colonizes in BAC can contribute to improving water treatment efficiency through the metabolism of nutrients and organics (Li D. et al, 2017).…”
Section: Discussionmentioning
confidence: 99%